The ceramide moiety of disialoganglioside (GD3) is essential for GD3 recognition by the sialic acid–binding lectin SIGLEC7 on the cell surface - Hashimoto, Noboru (J Biol Chem, 2019)
To analyze the binding specificity of a sialic acid–recognizing lectin, sialic acid-binding Ig-like lectin 7 (SIGLEC7), to disialyl gangliosides (GD3s), here we established GD3-expressing cells by introducing GD3 synthase (GD3S or ST8SIA1) cDNA into a colon cancer cell line, DLD-1, that expresses no ligands for the recombinant protein SIGLEC7-Fc. SIGLEC7-Fc did not recognize newly-expressed GD3 on DLD-1 cells, even though GD3 was highly expressed, as detected by an anti-GD3 antibody. Because milk-derived GD3 could be recognized by this fusion protein when incorporated onto the surface of DLD-1 cells, we compared the ceramides in DLD-1–generated and milk-derived GD3s to identify the SIGLEC7-specific GD3 structures on the cell membrane, revealing that SIGLEC7 recognizes only GD3-containing regular ceramides but not phytoceramides. This was confirmed by knockdown/knockout of the sphingolipid delta(4)-desaturase/C4-monooxygenase (DES2) gene, involved in phytoceramide synthesis, disclosing that DES2 inhibition confers SIGLEC7 binding. Furthermore, knocking out fatty acid 2-hydroxylase also resulted in the emergence of SIGLEC7 binding to the cell surface. To analyze the effects of binding between SIGLEC7 and various GD3 species on natural killer function, we investigated cytotoxicity of peripheral blood mononuclear cells from healthy donors toward GD3S-transfected DLD-1 (DLD-1–GD3S) cells and DLD-1–GD3S cells with modified ceramides. We found that cytotoxicity is suppressed in DLD-1–GD3S cells with dehydroxylated GD3s. These results indicate that the ceramide structures in glycosphingolipids affect SIGLEC7 binding and distribution on the cell surface and influence cell sensitivity to killing by SIGLEC7-expressing effector cells.